Relationship between safety management practices and safety behaviour among production workers in one of the steel drum company - Lim, Sin Pei (2017)
Safety management practices are the essential elements to ensure effectiveness in safety management in a company. This study is to determine the level of safety behaviour among production workers and identify the relationship between safety management practices and safety behaviour in company among production workers. The study was conducted by survey. A total of 117 respondents that returned the questionnaire. The result of this study implies that the level of safety behaviour among production workers was high (mean value is 3.72 for safety compliance and 4.08 for safety participation). The findings of the study also revealed that management commitment, safety training and safety communication and feedback have significantly influence safety compliance, while safety rules and procedures have significantly influence safety participation. The findings of the study will provide a good reference to the company to further improve their safety management practices in order to increase the level of safety behaviour among workers.